Sequence and phylogenetic analysis of Newcastle disease virus genotype VII isolated in Malaysia during 1999-2012 - Shohaimi , Syamsiah Aini; Ahmad Raus, Raha; Ong , Geok Huai; Mohamed Asmayatim, Basirah; Nayan, Nursyuwari; Mat Yusof, Afzan (Universiti Teknologi Malaysia, 2015)
Newcastle disease virus (NDV) is a contagious viral disease of many avian species particularly domestic poultry, and is responsible for causing significant economic losses to the poultry industry in Southeast Asia including Malaysia. Here we report the sequence and phylogenetic analysis of NDV that has been circulating in Malaysia. A total of 151 NDV isolates were selected during 1999-2012 throughout Malaysia and were characterized phylogenetically. The partial region of matrix (M) and fusion (F) protein of NDV was amplified by reverse transcriptase PCR, directly sequenced and compared genetically to the published sequences obtained from GenBank. The deduced amino acid sequence of the F protein cleavage site revealed the presence of three different motifs; 112RRRKRF117, 112RRQKRF117 typical for velogenic strains while 112GKQGRL117 indicates it is from avirulent strain or lentogenic strain. The phylogenetic analysis revealed that 13 isolates belonged to genotype I, 2 to genotype III, 6 to genotype VI, 1 to genotype VIII and 129 to genotype VII. Isolates belonging to genotype VII were further divided into five subgenotypes; VIIa, VIIb, VIId, VIIe and VIIh. Based on the phylogenetic tree and geographical data, it is found that NDV genotype VIIb and VIIe were isolated in 1999 while in year 2000 to 2009, most of the NDV isolates were NDV genotype VIId originated from China. No subgenotype VIId viruses were recovered after 2009 in Malaysia. In 2010-2012, NDV outbreaks were caused by subgenotypes VIIa and VIIh in Peninsular Malaysia. Interestingly, these subgenotypes have been isolated in East Malaysia since 2002 but did not cause major outbreak. These information points to the existence of multiple genotypes of NDV in Malaysia especially genotype VII and these findings emphasize the importance of continuous surveillance of NDV in Malaysia.